Tumour-cell-induced endothelial cell necroptosis via death receptor 6 promotes metastasis - Strilić, Boris; Han, Kang; Müller, Ulrike C. (Nature, 2016)
Human and murine tumour cells induce programmed necrosis (necroptosis) of endothelial cells, which promotes tumour cell extravasation and metastasis.
Das PDF enthält zusätzlich einen Anhang von 16 Seiten
Gesehen am 20.05.2020